(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It is a universal phenomenon that each individual is concerned with the satisfaction of profoundly felt needs and mitigating of torment. Well known otherworldly movements and their development spring from this universal longing (Albert Einstein1930 pp 1-4). Homeopathic enchantment had its impact in the prior days in alleviating the dread and torment of the general population. Unsatisfied with the aftereffect of alchemists, the antiquated individuals surrendered to the monks and ministers for supernatural power and direction to have a superior existence without physical and mental affliction. This holy standing made deceptive creatures for the common men to offer penances to satisfy divine beings (Sir James George Frazer1922). In the advanced field, the political pioneers and the religious position are abusing religion for their advantage. This article attempts to focus on how human love and relationship got choked and tangled up by the religious convictions in the contemporary society depicted in the novel Half of a Yellow Sun by Chimamanda Ngozi Adichie.